Resilience and evolution of microbial spatial self-organisation - Kow, Zi Shan (Nanyang Technological University, 2020)
Microbial communities produce fascinating patterns of spatial self-organization, and these patterns can have important effects on the metabolic and evolutionary processes acting on microbial communities. Presently, experimental research has been limited to the development of the initial spatial pattern rather than its evolutionary changes. There is also a lack of understanding regarding the resilience of spatial self-organization to environmental perturbations. The aim of this study is to investigate if spatial patterns can evolve and continue to persist after environmental changes. An evolutionary experiment was set up to visualize the growth patterns of two cross feeding isogenic Pseudonomas stutzeri A1501 strains in the denitrification process during spatial range expansion. Four evolutionary groups of co-cultures were set up with constant and alternating media at a pH of 6.5 and 7.5 to simulate mutualism and commensalism will be compared. The results of the study were largely unintuitive. No distinct differences were found between the spatial patterns of commensal and mutualistic groups, and the development of an expansion gap was found in majority of the lines in the constant group. In the fluctuating group, mutant spatial pattern was observed in nitrate conditions. This demonstrates for the first time the evolution of a spatial pattern to a distinctly different one. Moreover, the new novel spatial pattern remained stable and re-established every time after perturbation. This study has affirmed the potential for experimental evolution research in spatial self-organised systems and raised new questions for this field.